Estado nutricional, sintomas dispépticos e níveis de grelina em pacientes portadores de doença de Crohn : correlação com a atividade da doença - Sales, Kamila Maria Oliveira (2013)
5 ABSTRACT Weight loss is a common complaint of patients with Crohn's disease, malnu trition being present in 30 - 80% of those cases. It has been shown that patients with Crohn's disease in downtime related dyspeptic symptoms change in gastric emptying. However, the correlation of disease activity with anthropometric parameters, nutritional and satiety is still under investigation. Therefore, the aim of our study was to correlate disease activity with nutritional status, gastrointestinal symptoms, gastric emptying, satiety and ghrelin levels in patients with Crohn's disease. It is a cross - se ctional, analytical and quantitative performed in twenty patients with Crohn's disease, according to a classified Activity Index Crohn's disease (Crohn's Disease Activity Index - CDAI). The patients underwent a nutritional assessment, which was based on th e use of doubly indirect methods (body mass index, triceps skinfold thickness and arm circumference). Moreover, in patients was evaluated food intake through a diet record. These were also subjected to an analysis of gastric emptying by breath test using 1 3C - octanoic acid bound to a solid meal - and answered a validated questionnaire (Questionnaire Porto Alegre on dyspeptic symptoms) to assess dyspeptic symptoms. Another test was conducted satiety test (drinking test), in which the patient ate 15 ml of a liquid drink pattern (Nutridrink) and was asked what level of satiety via an analog scale. During the breath test, samples were taken blood samples for measurement of ghrelin: basal (fasting) and postprandial glucose. Data were analyzed statistically by te sts: Student t, Fisher's exact, Mann - Whitney and Spearman correlation. It was observed that the parameters CDAI and BMI (p = 0.0185) and CB (p = 0.023) were inversely proportional, but there was no statistical difference between the correlations of the CDA I with triceps skinfold (p = 0.0543). The patients did not correlate with disease activity gastric emptying (T ½ - p = 0.2533; t - lag p = 0.3079). However, there was a significant correlation with the CDAI all dyspeptic symptoms (p = 0.005). There was no co rrelation between disease activity and the volume of liquid supported. However, disease activity influence ghrelin levels in postprandial (p = .04). CONCLUSION: Disease activity correlates with nutritional status, the presence of dyspeptic symptoms and ghr elin levels in patients with Crohn's disease. However there is no correlation with changes in gastric emptying and satiety suggesting that other mechanisms may be involved